Are human leukocyte antigen complexes associated with risk to post-transplant diabetes mellitus? - Lucena, Débora Dias de; Marco, Renato de; Sá, João Roberto de; Medina-Pestana, José Osmar; Gerbase-DeLima, Maria; Rangel, Érika Bevilaqua (Brazilian Journal of Transplantation, 2021)
Introduction: Post-transplant diabetes mellitus (PTDM) increases both morbidity and mortality, resulting in cardiovascular complications in kidney transplanted recipients, and loss of renal graft. Risk factors for PTDM are divided into modifiable and non-modifiable. The impact of human leucocyte antigens (HLA) on PTDM is a subject of debate in the literature. Purpose: To verify prevalence of PTDM and its relationship with genetic factors. Methods: 450 patients who have undergone renal transplantation were investigated as to the association between HLA-A, -B and – DR antigens and PTDM. The frequencies of HLA-A, -B and -DR antigens were compared between recipients with and without PTDM diagnosis over three years after transplantation. Results: In the studied population, 60% were male, 47.2% were black and 57.8% received kidney from a deceased donor. PTDM was diagnosed in 61 patients (13.5%), 315 (70%) remained with normal blood glucose levels, and 74 (16.5%) developed impaired fasting blood glucose. Positive PTDM associations were observed in relation to HLA-A23 (18% vs 8.7%, P = 0.024) and HLA-A29 (13.1% vs 5.1%, P = 0.017), and negative association with HLA- A68 (4.9% vs 14.1%, P = 0.046). Conclusion: We found a statistical relationship between PTDM and HLA-A23, HLA-A29 and HLA-A68. However, further studies are needed to reach a final conclusion whether genetic susceptibility factors are associated with the development of PTDM.